If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4c + -3d = 7 Solving 4c + -3d = 7 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '3d' to each side of the equation. 4c + -3d + 3d = 7 + 3d Combine like terms: -3d + 3d = 0 4c + 0 = 7 + 3d 4c = 7 + 3d Divide each side by '4'. c = 1.75 + 0.75d Simplifying c = 1.75 + 0.75d
| 7h=-4 | | y+2x+12=2 | | -2x+(2+8x)=248 | | -31+x=1 | | 17=x-3x-3 | | 2z-24=6z | | F(3)=3+1 | | 2(15x)+30=50 | | 2f(4)=3(4)+2 | | 800+1300x=2620-100x | | 37=x-76 | | (y^3-4y^2-2)-(6y^3+4-6y^2)=0 | | 4x^3-10x^2=6x | | X-8.66=3.33 | | 4x^3-10x^2=6 | | 3x+(2x-5)= | | 25.72-20-5-0.02= | | (6a^2)*x^2-11ax=10 | | 5000-10p=-1000+5p | | 2(.625x)+2x=50 | | 9t-6-6t=76 | | .99x+19.95+65.32=144.67 | | 48=96 | | 7x+9x-69=115-7x | | 5-3r=r+2 | | 500-p=50+p | | 3y-7y=11 | | 6+8(1+2x)=110 | | (5x^2-3x+7x)+(9x^2+2x^2+7x)=0 | | 5a-12=24+2a | | 5p=200+20 | | -5.14+13.5d=18.99+15.4d+4.94 |